2011
DOI: 10.1158/1078-0432.ccr-10-1359
|View full text |Cite
|
Sign up to set email alerts
|

Troponin I and C-Reactive Protein Are Commonly Detected in Patients with Breast Cancer Treated with Dose-Dense Chemotherapy Incorporating Trastuzumab and Lapatinib

Abstract: Purpose: There are no validated methods of early detection of cardiotoxicity from trastuzumab (T) following anthracycline-based chemotherapy. Currently changes in left ventricular ejection fraction (LVEF) are assessed but this approach has limited sensitivity and specificity. Within a prospective feasibility study of dose-dense (dd) doxorubicin and cyclophosphamide (AC) ! weekly paclitaxel (P) with T and lapatinib (L), we included a preplanned analysis of correlative cardiac Troponin I (cTnI) and C-reactive pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(85 citation statements)
references
References 35 publications
1
81
2
1
Order By: Relevance
“…Furthermore, a value .30 pg/mL was associated with specificity of 73% and negative predictive value of 77% for subsequent CTRCD. In contrast, Morris et al 179 demonstrated that TnI increases in patients receiving both trastuzumab and the tyrosine kinase inhibitor lapatinib were common, occurring in 67% of individuals; these elevations were not associated with subsequent CTRCD as detected by serial MUGA scans. Schmidinger et al 180 also reported an increase in troponin T in 10%…”
Section: Figure 8 Speckle-tracking Echocardiographical Images Illustrmentioning
confidence: 90%
“…Furthermore, a value .30 pg/mL was associated with specificity of 73% and negative predictive value of 77% for subsequent CTRCD. In contrast, Morris et al 179 demonstrated that TnI increases in patients receiving both trastuzumab and the tyrosine kinase inhibitor lapatinib were common, occurring in 67% of individuals; these elevations were not associated with subsequent CTRCD as detected by serial MUGA scans. Schmidinger et al 180 also reported an increase in troponin T in 10%…”
Section: Figure 8 Speckle-tracking Echocardiographical Images Illustrmentioning
confidence: 90%
“…Three studies have reported that elevated and increasing troponin I following chemotherapy, particularly if such increase persists at 1 month after treatment,84 is associated with subsequent cardiac dysfunction as well as with lower likelihood of cardiac recovery in patients receiving trastuzumab 85, 86, 87. During treatment, negative cardiac troponin has a high negative predictive value; however, minute elevations can be commonly detected in patients following chemotherapy and have low positive predictive value 88. Additionally, optimal timing and frequency of measurement as well as the ideal cutoff have not yet been determined.…”
Section: Monitoring For Cardiac Dysfunction During Her2‐targeted Therapymentioning
confidence: 99%
“…In prospective study including ninety-five patients with breast cancer treated with dose-dense doxorubicin and cyclophosphamide, than weekly paclitaxel with trastuzumab and lapatinib, the levels of Creactive protein were measured every 2 weeks during chemotherapy then at months 6, 9 and 18. During chemotherapy a detectable C-reactive protein was seen in 78% but did not correlate with ejection fraction declines (Morris et al, 2010).…”
Section: C-reactive Proteinmentioning
confidence: 87%